History of the Department of Surgery at Albany Medical Center. Issue 3 (March 2013) - Conti, David J.; Lempert, Neil; Stain, Steven C.
Surgeons have always played an integral role in the history of the Albany Medical Center and Albany Medical College. In addition to supporting vital patient care and teaching programs, the Department of Surgery has played an important administrative role providing the college with five deans. The origins of the Department of Surgery reach back to 1910 when the American Medical Association-sponsored Flexner report proposed dramatic changes in the structure and format of medical education in the United States. In response to the recommendations of the report, the medical center restructured its faculty and curriculum to meet the demands of a rapidly advancing profession. One result of this reorganization was the formation of the Department of Surgery in 1912. Dr. Arthur Elting was named the first Chair of the Department in 1915. This report will review the history of the Department, focusing on the eight surgeons who have served as Chair.